On the Efficiency of a Competitive Monetary Equilibrium with Transaction Costs - Honkapohja, S. (Review of Economic Studies, 1978)
Journal Article On the Efficiency of a Competitive Monetary Equilibrium with Transaction Costs Get access Seppo Honkapohja Seppo Honkapohja Yrjö Jahnsson Foundation and University of Helsinki Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 3, October 1978, Pages 405–415, https://doi.org/10.2307/2297243 Published: 01 October 1978 Article history Received: 01 February 1976 Accepted: 01 May 1977 Published: 01 October 1978